2012
DOI: 10.1100/2012/239271
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ozonation Process for the Reduction of Excess Sludge Production from Activated Sludge Process of Sago Industry Wastewater Using Central Composite Design

Abstract: Sago industries effluent containing large amounts of organic content produced excess sludge which is a serious problem in wastewater treatment. In this study ozonation has been employed for the reduction of excess sludge production in activated sludge process. Central composite design is used to study the effect of ozone treatment for the reduction of excess sludge production in sago effluent and to optimise the variables such as pH, ozonation time, and retention time. ANOVA showed that the coefficient determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, a contact time of 20 min was adequate to achieve maximum COD solubilisation when ozone dosage was 0.37 g O 3 /g SS. Similarly, Subha and Muthukumar (2012) observed that increasing contact time from 1 to 12 minutes maximized VSS reduction to 81%, but beyond this period the VSS reduction decreased to 32% due to the activity of radical scavengers.…”
Section: Ozone Concentration Flow Rate and Contact Timementioning
confidence: 97%
See 1 more Smart Citation
“…However, a contact time of 20 min was adequate to achieve maximum COD solubilisation when ozone dosage was 0.37 g O 3 /g SS. Similarly, Subha and Muthukumar (2012) observed that increasing contact time from 1 to 12 minutes maximized VSS reduction to 81%, but beyond this period the VSS reduction decreased to 32% due to the activity of radical scavengers.…”
Section: Ozone Concentration Flow Rate and Contact Timementioning
confidence: 97%
“…Manterola et al, (2008) did not observe any significant change in the soluble COD of sludge after ozonation at different HRTs (10-57 min), which meant that a short HRT (e.g., 10 min) was sufficient to reach maximum sludge solubilisation. Other studies caution that increasing contact time may in fact reduces sludge reduction due to the formation of radical scavengers (Naso et al, 2008;Subha & Muthukumar, 2012). Naso et al, (2008) varied the ozone contact time (0-30 min) at different ozone dosages, and found that 30 min resulted in the maximum COD solubilisation at the ozone range of 0.05-0.07 g O 3 /g SS.…”
Section: Ozone Concentration Flow Rate and Contact Timementioning
confidence: 99%
“…RSM is an experiential, modeling and analysis engineering technique used to evaluate the relationship between a set of controllable experimental factors and observed results (Subha and Muthukumar, 2012). Experiments aimed to study the effect of BSB size, BSB distance, and time on COD and VS reduction were chosen.…”
Section: Fitting the Second Order Polynomial Equation And Statisticalmentioning
confidence: 99%
“…Once dissolved in water, the ozone reacts with a large number of organic compounds in two different possible ways: direct oxidation, such as molecular ozone, or indirect reaction through the formation of secondary oxidants, such as free radicals, particularly the hydroxyl radical (Subha and Muthukumar, 2012;Wajahat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%